Reading Literacy Assessment in Philippine Basic Education: A Cross-Sectional, School-Based Phil-IRI Study - Funa, Aaron; Balisoro, Julie Ann; Gabay, Renz Alvin (Journal of Basic Education Research, 2025)
Purpose of the study: To examine whether age, sex, and grade level are associated with Philippine Informal Reading Inventory (Phil-IRI) performance in junior high school. Methodology: Cross-sectional, ex post facto analysis of n = 200 Grade 7–10 students (SY 2024–2025). Phil-IRI (Filipino) post-test scores were compared using Mann–Whitney U (sex) and Kruskal–Wallis H (age bands; grade levels), α = .05. Main Findings: Sex was associated with Phil-IRI scores: females outperformed males (Mdn = 26 vs 19; p < .001). No differences were found by age (p = .087) or grade (p = .513). Descriptives showed a small, lower-performing oldest age band and non-monotonic medians across grades, indicating variation occurs mainly within rather than between grades. Novelty/Originality of this study: Phil-IRI outcomes in this cohort relate to sex, not to age or grade. Schools should prioritize within-grade, profile-based supports using Phil-IRI decision levels and implement boy-responsive engagement, while monitoring older learners who remain below independence.